Transposition of Aromaticity from a Furan to a Cyclohexane Ring in Furoisoindoles During the Interaction of 3-(Furyl)allylamines with Bromomaleic Anhydride - Alekseeva, Kseniia A.; Kvyatkovskaya, Elizaveta A.; Nikitina, Eugeniya V.; Zaytsev, Vladimir P.; Eroshkina, Svetlana M.; Shikhaliev, Khidmet S.; Truong, Hieu H.; Khrustalev, Victor N.; Zubkov, Fedor I. (Synlett, 2020)
An unexpected four-step reaction sequence was discovered in the course of investigation of the interaction between 3-(furan-2-yl)allylamines and bromomaleic anhydride. This conversion begins with the initial N-acylation of the allylamines by the anhydride, followed by intramolecular Diels–Alder reaction, which is accompanied by a dehydrohalogenation, and ends with the formation of partially unsaturated furo[2,3-f]isoindoles followed by transposition of aromaticity from the furan moiety to the neighboring cyclohexane ring. The reaction between 3-(furan-3-yl)allylamines and bromomaleic anhydride does not stop at a furo[2,3-f]isoindole formation step, but proceeds further with the cleavage of the furan ring in a 100% atom-efficient fashion to provide polysubstituted isoindoline-4-carboxylic acids.
Keywords: furan; Diels–Alder reaction; transposition of aromaticity; furo[2,3-f]isoindole; IMDAV reaction; atom-efficient reaction